2019
DOI: 10.1016/j.isprsjprs.2018.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of photogrammetric accuracy by modeling and correcting the thermal effect on camera calibration

Abstract: This paper presents a new method for improving the geometric accuracy of photogrammetric reconstruction by modeling and correcting the thermal effect on camera image sensor. The objective is to verify that when the temperature of image sensor varies during the acquisition, image deformation induced by the temperature change is quantifiable, modelisable and correctable. A temperature sensor integrated in the camera enables the measurement of image sensor temperature at exposure. It is therefore natural and appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
(18 reference statements)
3
15
0
Order By: Relevance
“…The focal length of the last image (5513.48 pixels) is 3.10 pixels greater then that of the first image (5510.38 pixels). According to the relation between the focal length and the camera internal temperature given by Reference [31], an increase of 3.10 pixels corresponds to a temperature increase of around 40 • C for a focal length of 35 mm as in our experiments. The amplitude of the temperature variation is realistic and conforms to real acquisition conditions.…”
Section: Gradually Varied Focal Lengthsupporting
confidence: 65%
See 2 more Smart Citations
“…The focal length of the last image (5513.48 pixels) is 3.10 pixels greater then that of the first image (5510.38 pixels). According to the relation between the focal length and the camera internal temperature given by Reference [31], an increase of 3.10 pixels corresponds to a temperature increase of around 40 • C for a focal length of 35 mm as in our experiments. The amplitude of the temperature variation is realistic and conforms to real acquisition conditions.…”
Section: Gradually Varied Focal Lengthsupporting
confidence: 65%
“…It is not certain that the focal length increases linearly in real life. Actually, as shown in Reference [31], the increment speed of the temperature decreases with time and the focal length increases linearly with the temperature. Here, the linear model is chosen to model the focal length variation for its simplicity of interpretation.…”
Section: Gradually Varied Focal Lengthmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, the thermal image can be unreliable especially when the internal temperature of the camera is changing rapidly, such as during camera warmup period or during the flight when a gust of cool wind results in cooling of the camera. To overcome this challenge, the user may need to provide sufficient startup time before operation (preferably 30-60 min) [102,[143][144][145], shield the camera to minimize the change in the internal temperature of the camera [142], calibrate the camera [146][147][148][149][150][151][152][153], and perform frequent flat-field corrections.…”
Section: Thermalmentioning
confidence: 99%
“…The research has showed out that in some cameras the focal length and principal point position are changing in several dozen of microns, although between calibration the camera was not operationally used. It is worth underlining that also thermal conditions impact the parameters of interior orientation (Daakir, 2019).…”
Section: Intoroductionmentioning
confidence: 99%